Harassment and attacks on human rights activists in Palestine are rarely punished. - Stein, Sam (The Progressive Magazine, 2023)
A recent trial of an attack by an Israeli settler on a U.S. citizen shows how difficult it is to obtain justice when harassment and attacks on human rights activists are committed.
Keywords: 2023-10 October; Israel